Successful Treatment of Multiple Multidrug Resistant Intracranial Tuberculomata - Richard P. Sullivan; Hazel F. Goldberg; Ross S. Mellick; Jeffrey J. Post (Case Reports in Infectious Diseases)
A 21-year-old Bangladesh-born man presented with a month history of evolving neurological symptoms in the context of a six-month history of fever, night sweats, and axillary lymphadenopathy. He was subsequently diagnosed with multiple multidrug resistant intracranial tuberculomata and was successfully treated over two years. Intracranial multidrug resistant tuberculosis has a high mortality and successful treatment is rarely reported. Management is complex and requires consideration of the penetration and likely effect of antituberculous agents within the central nervous system. We discuss the role of various antituberculous agents, the duration of therapy, the utility of corticosteroids, the value of intrathecal and systemic therapy, and the need for rapid diagnosis.